Magnetic alginate microparticles for purification of alpha-amylases - Safaríková, M; Roy, I; Gupta, M N; Safarík, I (Journal of biotechnology, 2003)
Spherical magnetic alginate microparticles (25-60 microm in diameter) were prepared using the microemulsion system, with water-saturated 1-pentanol as the organic phase. The limited solubility of 1-pentanol in water enabled simple removal of the organic solvent from the prepared beads with water solution. The prepared alginate microparticles were used as magnetic affinity adsorbents for specific purification of alpha-amylases. Enzyme activity was eluted by 1.0 M maltose. alpha-Amylases from Bacillus amyloliquefaciens and porcine pancreatic acetone powder were purified 9- and 12-fold with 88 and 96% activity recovery, respectively.
Keywords: Protein Binding; mikrosféry; algináty; magnetismus; Microscopy, Electron, Scanning; alpha-Amylases; Hydrogen-Ion Concentration; koncentrace vodíkových iontů; Magnetics; mikroskopie elektronová rastrovací; Alginates; Microspheres; vazba proteinů; alfa-amylasy